Highly Effective Ex Vivo Gene Manipulation to Study Kidney Development Using Self-Complementary Adenoassociated Viruses - Tie-Lin Chen; Hong-Lian Wang; Yun-Hong Liu; Yin Fang; Rui-Zhi Tan; Pu-Hui Zhou; Qin Zhou; Xiao-Yan Lv (The Scientific World Journal)
Background. Ex vivo culture of intact embryonic kidney has become a powerful system for studying renal development. However, few methods have been available for gene manipulation and have impeded the identification and investigation of genes in this developmental process. Results. Here we systemically compared eight different serotypes of pseudotyped self-complementary adenoassociated viruses (scAAVs) transduction in cultured embryonic kidney with a modified culture procedure. We demonstrated that scAAV was highly effective in delivering genes into and expressing in compacted tissues. scAAV serotypes 2 and 8 exhibited higher efficiency of transduction compared to others. Expression kinetics assay revealed that scAAV can be used for gene manipulation at the study of UB branching and nephrogenesis. Repressing WT1 in cultured kidney using shRNA impairs tubule formation. We for the first time employed and validated scAAV as a gene delivery tool in cultured kidney. Conclusions. These findings are expected to expedite the use of the ex vivo embryonic kidney cultures for kidney development research. For other ex vivo cultured organ models, scAAV could also be a promising tool for organogenesis study.